2010
DOI: 10.4240/wjgs.v2.i3.78
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of complicated hydatid cysts of the liver

Abstract: AIM:To review the clinical presentation and surgical management of complicated hydatid cysts of the liver and to assess whether conservative surgery is adequate in the management of complicated hydatid cysts of liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 13 publications
2
46
0
Order By: Relevance
“…3,4 Most common clinical presentation was abdominal pain (65%), which is comparable with previous studies of Malik et al (76.81%) and Akther et al (89.47%). 5,6 Right lobe of liver was most commonly involved (75%), which is similar to studies of Malik et al (65.2%) and Akther et al (62.5%). 5,6 Majority of cysts are single (90%), comparable to previous studies of Safioleas et al (60.6%) and Kalinova et al (84.25%).…”
Section: Discussionsupporting
confidence: 80%
“…3,4 Most common clinical presentation was abdominal pain (65%), which is comparable with previous studies of Malik et al (76.81%) and Akther et al (89.47%). 5,6 Right lobe of liver was most commonly involved (75%), which is similar to studies of Malik et al (65.2%) and Akther et al (62.5%). 5,6 Majority of cysts are single (90%), comparable to previous studies of Safioleas et al (60.6%) and Kalinova et al (84.25%).…”
Section: Discussionsupporting
confidence: 80%
“…8,10 Similarly, Mohan SVS et al reported a diagnostic accuracy of 90% and 100% for ultrasound an CT scan respectively. 9 Sayek and his colleagues also used ultrasound abdomen and CT scan abdomen to confirm the diagnosis of hydatid cyst. 15 When ultrasound and CT scan do not provide the necessary information, especially in case of extrahepatic cysts or the serological tests are inconclusive, then MRI can be used as an alternative diagnostic modality for the diagnosis of hydatid disease.…”
Section: Discussionmentioning
confidence: 99%
“…This figure is slightly higher than 4.3% reported in other studies. 8,9 Radical surgery, pericystectomy or liver resection has lower risk of recurrence than conservative procedures (partial cystectomy, unroofing, capitonnage, omentoplasty).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations